Takane & Hana. Volume 10 - Shiwasu, Yuki; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2019)
"After her older sister refuses to go to an arranged marriage meeting with Takane Saibara, the heir to a vast business fortune, high schooler Hana Nonomura agrees to be her stand-in to save face for the family. But when these two utter opposites pair up, get ready for some sparks to fly! When Hana's childhood friend Okamon confesses that he's in love with her, Hana goes into a total panic! Can she possibly return his feelings? And once Takane finds out, all bets are off on how he'll react to the news!"--Page [4] of cover.